Pengaruh Perceived Organizational Support terhadap Organizational Citizenship Behavior dengan Komitmen Organisasional sebagai Variabel Mediasi pada Perawat Rawat Inap Rumah Sakit Tentara Dr. Reksodiwiryo Padang - Suci Wulandari; Chichi Andriani (Universitas Negeri Padang, 2019)
Abstractpurpose of this study was to analyze: (1) The effect of perceived organizational support on organizational citizenship behavior in inpatient nurses at Tentara Dr. Reksodiwiryo Padang Hospital’s, (2) Organizational commitment as mediator on the effect of perceived organizational support on organizational citizenship behavior in inpatient nurses at Tentara Dr. Reksodiwiryo Padang Hospital’s. The population of this study was all inpatient nurses at Tentara Dr. Reksodiwiryo Padang Hospital’s which numbered 137 people. While the number of research samples is 102 people using cluster proportional random sampling technique. The analysis technique used is SEM analysis using SmartPLS 2.0.The results of the study show that: (1) Perceived organizational support has a positive and significant effect on organizational commitment to inpatient nurses at Tentara Dr. Reksodiwiryo Padang Hospital’s, (2) Organizational commitment has a positive and significant effect on organizational citizenship behavior in inpatient nurses at Tentara Dr. Reksodiwiryo Padang Hospital’s, (3) Perceived organizational support has a positive and significant effect on organizational citizenship behavior in inpatient nurses at Tentara Dr. Reksodiwiryo Padang Hospital’s, (4) Organizational commitment significantly mediates the relationship between perceived organizational support to organizational citizenship behavior in inpatient nurses at Tentara Dr. Reksodiwiryo Padang Hospital’s. Keywords: Organizational Citizenship Behavior, Perceived Organizational Support, and Organizational commitment